EFFICIENCY OF USING DIRECT LEXICAL EQUIVALENTS IN TRANSLATING HISTORICISMS - Lasinska, Tatiana (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article investigates the effectiveness of using direct lexical equivalents in translating historicisms. The peculiarities of translating historicisms are examined and the factors that influence the choice of lexical equivalents are identified. The problems that arise when using direct lexical equivalents, such as inappropriate associations and connotations due to cultural differences, are explored. Various methods of reproducing connotations and associative fields of English historicisms in Ukrainian, such as the use of synonyms and descriptive translation, are proposed. Based on the analysis of examples from English and Ukrainian literature, conclusions are drawn about the effectiveness of different approaches to reproducing historicisms. Personal contribution: analysis of literature and examples of translating historicisms, as well as formulated conclusions regarding the effectiveness of using different methods of translating historicisms. ____________ References: • Scott, W. Ivanhoe (Ware, Wordsworth Edition Ltd, 1995), 390. • Skott, Ajvengo, per. z angl. I. Davydenko (Kyi’v, Krai’na Mrij, 2014), 400. • Skott, Ajvengo, per. z angl. Ju. Lisnjaka ta G. Lozyns’koi’ (Kyi’v, Shkola, 2007), 494. • https://uk.wikipedia.org/wiki/Dzhura.